Analisis Loyalitas Pelanggan dilihat dari Kualitas Produk dan Harga pada Pelanggan Rokok Gudang Baru Malang - Mochamad Ridwan El Ghoni; Ismi Iftikad (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
This study aims to determine: 1) The positive effect of product quality on customer loyalty, 2) The positive effect of price on customer loyalty, 3) The influence of product quality and price simultaneously or together on customer loyalty Cigarettes Gudang Baru, Kepanjen, Malang Regency. The sampling technique used was random sampling. Data was obtained by distributing questionnaires about product quality, price, and customer loyalty to 100 respondents. Data analysis using Multiple Regression Test. The results of the study show 1) Service quality has a positive effect on customer loyalty, 2) Price has no effect on customer loyalty, 3) Service quality and price simultaneously or jointly affect customer loyalty for Gudang Baru cigarettes